Severe hypoglycemia in a 14-year-old adolescent with negative imaging tests and inconclusive intra-arterial calcium stimulation test. - García-Ruiz, Víctor Raúl (2024)
Introduction: Insulinoma is the most frequent cause of acquired hypoglycemia. Tumor localization with auxiliary images is possible in many patients, and it is necessary to resort to other methods in the rest. Report: 14-year-old adolescent with seizure and glucose 22mg/dl; insulin at 62UI/ml, C-peptide: 9.4ng/ml, compatible with hyperinsulinemic hypoglycemia. Tomography, magnetic resonance imaging of the pancreas, and echoendoscopy are negative. An intra-arterial stimulation test with calcium (TEIC) was performed, which showed less than a double elevation of insulin in the splenic artery. Given the inconclusive result, a body-tail subtotal pancreatectomy was decided. Pathological anatomy reports: 0.7cm tumor compatible with insulinoma. Discussion: Insulinoma should always be considered as a diagnostic possibility in all hyperinsulinemic hypoglycemia. There is no defined protocol to follow in case of inconclusive TEIC; making use of other markers such as C-peptide, repeating this, analyzing the number of times that insulin rises with respect to baseline would be an alternative.